A Flipbook on Waste Recycling Based on the Problem-Based Learning Model: An Effort to Improve Students’ Understanding of Explanatory Texts - Lintang Luthfiana; Panca Dewi Purwati (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to: (1) describe the design of a flipbook media for teaching explanatory text comprehension; (2) present the results of the flipbook's feasibility testing; and (3) analyze its effectiveness in enhancing students’ understanding of explanatory texts. Methodology: The research employed the Research and Development (R&D) method using the Borg & Gall model, encompassing the stages of analysis, design, development, implementation, and evaluation. The study was conducted at Elementary School Nongkosawit 01, Semarang City, involving both teacher and student participants. Main Findings: The developed flipbook was designed to be visually appealing, pedagogically relevant, and responsive to the needs of teachers and students. Feasibility testing yielded very high validation scores 93.00% from media experts and 95.00% from material experts placing it in the “very feasible” category. Teacher and student responses indicated that the flipbook significantly supported engagement and comprehension. Effectiveness trials showed improvement rates of 84.16% in small-scale and 81.26% in large-scale trials, confirming its suitability for Grade V explanatory text learning. Novelty/Originality of this study: The innovation of this study lies in the integration of Problem-Based Learning (PBL) with locally relevant recycled waste content into a digital flipbook format. This combination not only strengthens students’ mastery of explanatory texts but also embeds values of responsibility, environmental care, and sustainability. By contextualizing literacy learning with environmental education, the flipbook serves as both an academic and character-building tool. This model provides a replicable, culturally grounded, and eco-conscious approach to literacy instruction in primary schools.